Managerial bonuses and subordinate mistreatment [dataset] - Nikiforakis, Nikos; Oechssler, Joerg; Shah, Anwar (Universität, 2019)
Can performance bonuses increase the likelihood that managers coerce their subordinates into exerting high levels of effort when doing so promotes ...